A REVIEW OF THE EFFECT OF ADDITIVES ON THE MECHANICAL PROPERTIES OF LIGHTWEIGHT CONCRETE - Raed K. Mohammed Jawad; Mohammed J. Kadhim; Hamza M. Kamal (Journal of Engineering and Sustainable Development, 2023)
Many organizations around the world have recognized lightweight, long-lasting, cost and environmentally-friendly construction materials as a future necessity. The lightweight concrete is manufactured mainly either by replacing the original aggregate with lightweight aggregate or addition foam production materials to concrete mixtures. These additions lead to a decrease in the lightweight concrete density and change mechanical properties such as compressive strength. Therefore, there is much experimental research has been conducted to add different material types that can improve lightweight concrete compressive strength while maintaining low density. In this review, the effect of various additions such as steel fiber, product waste materials, and nano-materials on the lightweight concrete compressive strength and density have been explained. The various effects of these additive materials on lightweight concrete properties, some additives lead to improving the properties of lightweight concrete, while other materials lead to a decrease in those properties, and this depends on the type and amount of material additive, the method lightweight concrete manufacturing, and their mixture composition.